Phototaxis of Halobacterium salinarium requires a signalling complex of sensory rhodopsin I and its methyl-accepting transducer HtrI. - Krah, M (1994)
Sensory rhodopsin I (SRI) is a photoreceptor that mediates phototaxis in the archaeon Halobacterium salinarium. Receptor excitation is relayed to the motility system of the cell by the methyl-accepting transducer protein HtrI. In membranes prepared from cells that lack HtrI the absorbance difference maximum of SRI was shifted from 587 to 565 nm. The thermal decay of the metastable photocycle intermediate SRI373 was measured as time-dependent recovery of the absorbance at 590 nm. In the absence of HtrI the decay was slowed down by two orders of magnitude. When SRI was overproduced in cells that contained normal levels of HtrI, the decay of SRI373 was biexponential indicating two kinetically distinct species. Spectroscopic measurements on intact cells revealed the same effect of HtrI on SRI photocycling as found in isolated membranes. By transient exposure of membranes from wild-type cells to low ionic strength, the decay of SR373 was slowed to the same value found for untreated membranes in the absence of HtrI. In parallel, the absorbance difference maximum was shifted to 565 nm indicating that a physical interaction of HtrI and SRI had been irreversibly destroyed. Overproduction of SRI in the presence of wild-type amounts of HtrI did not increase the light sensitivity of the cells to orange light step down stimulation. It is concluded that SRI and HtrI form a stable complex in the cell membrane that signals to the flagellar motor and defines absorbance maximum, photocycling rate and photochemical efficiency of SRI.